Application of Pressure and Release Model to Assess Flood Impact in Mitondo Area, Chikwawa District, Malawi - Pengapenga , Calvin; Mzuza , Maureen Kapute (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 8, 2023)
The study analysed the flood impact in the Mitondo area regarding the Pressure and Release (PAR) model. The PAR model depicts a disaster as a product of physical exposure and socioeconomic Pressure. The model has three components generating Vulnerability on the social side, namely root causes, dynamic Pressure, and unsafe conditions. The study aimed to identify the impact that floods have had on people's socioeconomic status, to establish the most vulnerable groups during floods regarding gender and to identify coping mechanisms employed during floods. The study used a descriptive cross-sectional research design. Most prone flood villages were selected, participants were sampled using purposive sampling, and data were analysed using SPSS and Microsoft Excel. The study results revealed that the prevailing vulnerabilities during the floods were rooted in various factors, ranging from poverty, lack of resources, lack of strong infrastructure, and lack of early warning systems, as depicted by the stages of the PAR model. These factors resulted from the individual, community, and national Government's mistakes. There is still more to be done on the progression to the safety model. The current efforts in Mitondo are only based on and aiming at controlling the situation. For example, people must relocate to safe locations, build hazard-resistant buildings and infrastructure, increase low incomes, and embark on a disaster preparedness plan to achieve safe conditions. The study recommended that Government and key stakeholders should civic educate people in Mitondo who reside in flood-prone areas in order for them to move permanently to higher grounds. The relocating should go with the provision of all the necessary socio amenities such as schools, hospitals, infrastructure, water, and agriculture support for three years to enable the households to settle. Furthermore, the district council must develop response and recovery plans for flood hazards in line with its disaster risk management plans and integrate them with its contingency plans.